Determinants of Rattan Industry Profitability in Cirebon, West Java - Septianingsih, Hesti; Istiqomah, Istiqomah; Floresti, Dwita Aprilia (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This study aims to analyze the determinants of profit received by rattan handicraft home industries in Rattan Galmantro Tourism Village, Tegalwangi Village. The independent variables include capital, labor, product variety, digital marketing and technology. This study took a sample of 70 respondents selected through simple random sampling. The data is analyzed using income analysis and multiple linear regression. The results show that capital, labor and technology have a significant positive effect on profit while product variety and digital marketing do not have a significant effect on the profits of the rattan handicraft home industry in the Galmantro Rattan Tourism Village, Tegalwangi Village.